Age disparities in stage‐specific colon cancer survival across seven countries: An International Cancer Benchmarking Partnership SURVMARK‐2 population‐based study. Issue 7 (14th October 2020) - Pilleron, Sophie; Charvat, Hadrien; Araghi, Marzieh; Arnold, Melina; Fidler‐Benaoudia, Miranda M.; Bardot, Aude; Guren, Marianne Grønlie; Tervonen, Hanna; Little, Alana; O'Connell, Dianne L.; Gavin, Anna; De, Prithwish; et al.
Abstract: We sought to understand the role of stage at diagnosis in observed age disparities in colon cancer survival among people aged 50 to 99 years using population‐based cancer registry data from seven high‐income countries: Australia, Canada, Denmark, Ireland, New Zealand, Norway and the United Kingdom. We used colon cancer incidence data for the period 2010 to 2014. We estimated the 3‐year net survival, as well as the 3‐year net survival conditional on surviving at least 6 months and 1 year after diagnosis, by country and stage at diagnosis (categorised as localised, regional or distant) using flexible parametric excess hazard regression models. In all countries, increasing age was associated with lower net survival. For example, 3‐year net survival (95% confidence interval) was 81% (80‐82) for 50 to 64 year olds and 58% (56‐60) for 85 to 99 year olds in Australia, and 74% (73‐74) and 39% (39‐40) in the United Kingdom, respectively. Those with distant stage colon cancer had the largest difference in colon cancer survival between the youngest and the oldest patients. Excess mortality for the oldest patients with localised or regional cancers was observed during the first 6 months after diagnosis. Older patients diagnosed with localised (and in some countries regional) stage colon cancer who survived 6 months after diagnosis experienced the same survival as their younger counterparts. Further studies examining other prognostic clinical factors such as comorbidities and treatment, and socioeconomic factors are warranted to gain further understanding of the age disparities in colon cancer survival. Abstract : What's new? Survival rates for colon cancer have improved over the past few decades. However, survival rates can vary by as much as 35% between younger and older patients. In this study, the authors found that this "age gap" occurred primarily within the first year after diagnosis. Stage at diagnosis also had a greater impact for older patients. Early diagnosis and individualized management should thus help to reduce early mortality in older patients. Further studies on additional prognostic factors such as comorbidities, etc., are also warranted.